2021
DOI: 10.3390/medicina57080826
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Diaphragmatic Breathing with Cervical Spine Mobilization on the Pulmonary Function and Craniovertebral Angle in Patients with Chronic Stroke

Abstract: Background and Objectives: Patients with stroke have a forward neck posture due to neurological damage and often have impaired pulmonary function. This study investigated the effect of diaphragmatic breathing with cervical mobilization to improve pulmonary function cervical alignments. Materials and Methods: This study used a one-group pre-test–post-test design including 20 patients with stroke. Two types of cervical joint mobilization techniques, consisting of left and right lateral glide mobilization and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In our study, we achieved greater improvement in FHP scores in the SG using CM. A limited number of past studies have shown that CM may improve FHP, cervical position sense, swallowing function, and respiratory function in SI (An et al, 2021; An & Park, 2021; Jeon et al, 2020). These results are consistent with ours.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we achieved greater improvement in FHP scores in the SG using CM. A limited number of past studies have shown that CM may improve FHP, cervical position sense, swallowing function, and respiratory function in SI (An et al, 2021; An & Park, 2021; Jeon et al, 2020). These results are consistent with ours.…”
Section: Discussionmentioning
confidence: 99%